S49. COGNITIVE CORRELATES OF ABNORMAL MYELINATION IN PSYCHOSIS. (9th April 2019) - Vanes, Lucy; Mouchlianitis, Elias; Barry, Erica; Patel, Krisna; Wong, Katie; Shergill, Sukhi
Abstract: Background: Psychotic illness has consistently been associated with deficits in cognitive function and reduced white matter integrity in the brain. However, the link between white matter disruptions and deficits in distinct cognitive domains remains poorly understood. Methods: We assessed cognitive performance across a range of tasks (working memory, verbal fluency, and general intelligence quotient) as well as whole-brain white matter myelin water fraction (MWF) using multicomponent driven equilibrium single pulse observation of T1 and T2 (mcDESPOT) in recent-onset psychosis patients and age-matched healthy controls (HC). Mediation analyses were conducted in order to assess whether regionally specific MWF reductions in psychosis patients could account for group differences in performance in each individual cognitive domain. Results: Psychosis patients showed deficits in working memory, phonological and semantic fluency, general intelligence quotient and reduced MWF in the left temporal white matter compared to HC. MWF in the left inferior fronto-occipital fasciculus and inferior longitudinal fasciculus was positively associated with intelligence quotient and verbal fluency in patients, and fully mediated group differences in performance in both phonological and semantic verbal fluency. There was no association between working memory and MWF in the left temporal white matter. Negative symptoms demonstrated a negative association with MWF within the left inferior and superior longitudinal fasciculi. Discussion: These findings indicate that psychosis-related deficits in distinct cognitive domains, such as verbal fluency and working memory, are not underpinned by a single common dysfunction in white matter connectivity.